ESPEN guideline: Clinical nutrition in surgery. Issue 3 (June 2017) - Weimann, Arved; Braga, Marco; Carli, Franco; Higashiguchi, Takashi; Hübner, Martin; Klek, Stanislaw; Laviano, Alessandro; Ljungqvist, Olle; Lobo, Dileep N.; Martindale, Robert; Waitzberg, Dan L.; Bischoff, Stephan C.; et al.
Summary: Early oral feeding is the preferred mode of nutrition for surgical patients. Avoidance of any nutritional therapy bears the risk of underfeeding during the postoperative course after major surgery. Considering that malnutrition and underfeeding are risk factors for postoperative complications, early enteral feeding is especially relevant for any surgical patient at nutritional risk, especially for those undergoing upper gastrointestinal surgery. The focus of this guideline is to cover nutritional aspects of the Enhanced Recovery After Surgery (ERAS) concept and the special nutritional needs of patients undergoing major surgery, e.g. for cancer, and of those developing severe complications despite best perioperative care. From a metabolic and nutritional point of view, the key aspects of perioperative care include: integration of nutrition into the overall management of the patient avoidance of long periods of preoperative fasting re-establishment of oral feeding as early as possible after surgery start of nutritional therapy early, as soon as a nutritional risk becomes apparent metabolic control e.g. of blood glucose reduction of factors which exacerbate stress-related catabolism or impair gastrointestinal function minimized time on paralytic agents for ventilator management in the postoperative period early mobilisation to facilitate protein synthesis and muscle function The guideline presents 37 recommendations for clinical practice.